2015
DOI: 10.3174/ajnr.a4453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Collaterals on Clinical Presentation, Baseline Imaging, Complications, and Outcome in Acute Stroke

Abstract: BACKGROUND AND PURPOSE:Good CTA collaterals independently predict good outcome in acute ischemic stroke. Our aim was to evaluate the role of collateral circulation and its added benefit over CTP-derived total ischemic volume as a predictor of baseline NIHSS score, total ischemic volume, hemorrhagic transformation, final infarct size, and a modified Rankin Scale score Ͼ2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 36 publications
(55 reference statements)
9
57
0
Order By: Relevance
“…Our findings confirm the prognostic value of CBS for patients treated with IVT found in earlier studies [9][10][11][12] and further extends this finding to patients treated with IAT. Studies reporting the influence of thrombus length (measured on susceptibility weight imaging on magnetic resonance imaging) on recanalization rates after thrombectomy are conflicting.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings confirm the prognostic value of CBS for patients treated with IVT found in earlier studies [9][10][11][12] and further extends this finding to patients treated with IAT. Studies reporting the influence of thrombus length (measured on susceptibility weight imaging on magnetic resonance imaging) on recanalization rates after thrombectomy are conflicting.…”
Section: Discussionsupporting
confidence: 81%
“…Patients with a lower CBS have lower odds of reperfusion and larger final infarct volumes at follow-up in patients treated with IVT. [9][10][11][12] For patients treated with IAT, the association of CBS with treatment efficacy is still sparsely studied. A post hoc analysis of the IMS-III trial (Interventional Management of Stroke III) data showed that recanalization rates were consistent across occlusion locations in patients treated with IAT.…”
mentioning
confidence: 99%
“…38 A clot burden score of 0 indicates a complete multisegmental vessel occlusion, with lower scores validated to independently predict lower recanalization rates with IV tPA, larger infarcts, poor outcome, and risk of hemorrhagic transformation. [38][39][40] Based on the data acquired from recent endovascular trials, the AHA/ASA has granted a grade I/A recommendation to endovascular candidates only with an occlusion located in the M1 or terminal ICA. The remaining large-vessel arterial locations are designated class IIb/C.…”
Section: Intracranial Laomentioning
confidence: 99%
“…Both the regional leptomeningeal collateral and collateral score have been shown to independently predict poor outcome (mRS score >2), infarct volume, and propensity for hemorrhagic transformation in the setting of an acute occlusion. 39,42 The aforementioned evaluations of collateral status use a single conventional CTA maximal intensity projection image (single phase). Multiphase CTA is a technique that can be used to increase temporal resolution of collateral blood flow and more accurately depict the process when compared with the opposite hemisphere.…”
Section: Collateral Assessmentmentioning
confidence: 99%
“…Future studies investigating the sensitivity and specificity of each method/modality used to define ischemic core is essential. 16,19 Furthermore, studies investigating the relationship between the ischemic core volume and collaterals 20 should be pursued. The definitions of ischemic core will need to be revisited in populations of patients with ultra-fast reperfusion.…”
Section: Opportunities For Standardizationmentioning
confidence: 99%